On the XXI All-Ukrainian scientific Taliyiv readings - Hrechko, A. A.; Klieshch, A. A. (Man and Environment. Issues of Neoecology, 2025)
On October 31, 2025, the first conference of the newly established structural unit of V. N. Karazin Kharkiv National University – the Educational and Scientific Institute of Ecology, Green Energy and Sustainable Development – was held. The event, known as the XXI All-Ukrainian Scientific Taliyiv Readings, was traditionally organized by the Department of Environmental Monitoring and Nature Conservation.The conference was conducted online via the Zoom platform, which made it possible to involve a wide range of participants from various regions of Ukraine. The traditional plenary presentations focused on the following key themes: the impact of war on environmental components, contemporary issues of rational nature management and nature protection, assessment of the ecological state of environmental components and complexes, as well as scientific and educational challenges of ecology and nature conservation in Ukraine.Panel discussion held on the DOMANI project - "Development of microcredit ecosystems in Ukraine and Mongolia for a competitive and sustainable green economy".